O Zjawisku Rezonansu dla Półograniczonych Belek Sprężystych - Więckowski, J. (Engineering Transactions, 1959)
An analysis of forced harmonic steady-state vibration is presented with zero initial conditions (the total mechanical energy equal to zero at; the initial moment for semi-infinite elastic beams with single point of action of the external force and for longitudinal and torsional vibration). The characteristics of the reaction forces are determined for various locations of the external force or moment. These characteristics reduce to three coefficients: the coefficient of proportionality of forces proportional to the displacement, the coefficient of proportionality of forces proportional to the velocity, the coefficient of proportionality of forces proportional to the acceleration. It is shown that the resonance properties of semi-infinite beams are entirely different from those of finite beams. The phenomenon of dynamic obstacle is described, consisting in that the mechanical energy does not pass across the point where the external force acts for certain frequencies of forced vibration which constitute an infinite sequence. The topics of papers to come are discussed.